Advanced Continuous Flow Platform for On‐Demand Pharmaceutical Manufacturing. Issue 11 (31st January 2018) - Zhang, Ping; Weeranoppanant, Nopphon; Thomas, Dale A.; Tahara, Kohei; Stelzer, Torsten; Russell, Mary Grace; O'Mahony, Marcus; Myerson, Allan S.; Lin, Hongkun; Kelly, Liam P.; Jensen, Klavs F.; Jamison, Timothy F.; et al.
Abstract: As a demonstration of an alternative to the challenges faced with batch pharmaceutical manufacturing including the large production footprint and lengthy time‐scale, we previously reported a refrigerator‐sized continuous flow system for the on‐demand production of essential medicines. Building on this technology, herein we report a second‐generation, reconfigurable and 25 % smaller (by volume) continuous flow pharmaceutical manufacturing platform featuring advances in reaction and purification equipment. Consisting of two compact [0.7 (L)×0.5 (D)×1.3 m (H)] stand‐alone units for synthesis and purification/formulation processes, the capabilities of this automated system are demonstrated with the synthesis of nicardipine hydrochloride and the production of concentrated liquid doses of ciprofloxacin hydrochloride, neostigmine methylsulfate and rufinamide that meet US Pharmacopeia standards. Abstract : On‐demand pharmaceutical production : The capabilities of a second‐generation, compact, continuous flow platform for on‐demand pharmaceutical manufacturing are demonstrated with the synthesis of nicardipine hydrochloride and the production of concentrated liquid doses of ciprofloxacin hydrochloride, neostigmine methylsulfate and rufinamide that meet US Pharmacopeia standards.